Impact of retransfusion of blood processed in cell-saver on coagulation versus cardiopulmonary bypass: a prospective observational study using thromboelastography - Vymazal, Tomáš; Filaun, Martin; Horáček, Michal (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2015)
AIMS: To compare an impact of retransfusion of blood processed in cell-saver (CS) with that of cardiopulmonary bypass (CPB) on blood coagulation in patients undergoing cardiac surgery. METHODS: Prospective observational study using thromboelastography (TEG). RESULTS: TEG samples from 170 patients were analyzed. Cardiopulmonary bypass was used in 100 patients while 70 patients were operated off-pump. In 20 off-pump patients collected blood was processed by cell-saver and returned. In all patients clot formation after heparin neutralization by protamine was unimpaired. However, there was a significant increase in fibrinolysis defined by the TEG parameter Lysis time 30 min after the maximum amplitude of the clot was reached (Ly30) in groups with CPB or CS but this increase still did not exceed the threshold for clinical fibrinolysis (Ly30 > 7.5%). In the group without CPB there was no significant impact on coagulation. CONCLUSION: Surgery that avoids CPB and/or CS is the gentlest method for inducing blood coagulation.
Keywords: Cardiopulmonary Bypass; Thrombelastography; Retreatment; Blood Coagulation; tromboelastografie; kardiopulmonální bypass; lidé; prospektivní studie; pooperační krvácení; Blood Transfusion; hemokoagulace; Prospective Studies; opakovaná terapie; Postoperative Hemorrhage; krevní transfuze; Humans